Comparative-historical methods - Lange, Matthew (SAGE, 2013)
This bright, engaging title provides a thorough and integrated review of comparative-historical methods. It sets out an intellectual history of comparative-historical analysis and presents the main methodological techniques employed by researchers, including: Comparative-historical analysis ; Case-based methods ; Comparative methods ; Data, case selection & theory. Matthew Lange has written a fresh, easy to follow introduction which showcases classic analyses, offers clear methodological examples and describes major methodological debates. It is a comprehensive, grounded book which understands the learning and research needs of students and researchers.